Bacterial etiology and antibiotic susceptibility pattern of diabetic foot infections in Tabriz, Iran - Akhi, Mohammad Taghi; Ghotaslou, Reza; Asgharzadeh, Mohammad; Varshochi, Mojtaba; Pirzadeh, Tahereh; Memar, Mohammad Yousef; Zahedi Bialvaei, Abed; Seifi Yarijan Sofla, Hasan; Alizadeh, Naser (German Medical Science GMS Publishing House, 2015)
Aim: The aim of this study was to investigate anaerobic and aerobic bacteria profile and determination of antibiotic susceptibility pattern in aerobic bacteria.Method: Specimens were cultured using optimal aerobic and anaerobic microbiological techniques. Identification of bacterial isolates was performed by standard microbiological methods and antibiotic susceptibility testing was performed according to the guidelines of Clinical and Laboratory Standards Institute (CLSI).Result: 92 bacterial strains were isolated from 60 samples of diabetic foot ulcers. Predominant aerobic bacteria isolated from these infections were (28%) followed by Enterobacteriaceae family (24%) including (15%), spp. (4%), spp. (4%), and coagulase-negative spp. (17%),spp. (15%), (7%) and spp. (4%). No spp. were isolated and 4% obtained from anaerobic culture. All Gram-positive isolates were susceptible to linezolid while all Enterobacteriaceae showed sensitivity to imipenem.Conclusion: Most of DFIs specimens were poly microbial infection and predominant bacteria were and . These wounds may require use of combined antimicrobial therapy for initial management.